Value Addad Analysis Of The Pickling Fish Agroindustry In Muncar District Banyuwangi Regency - Lailika, Dina Nurul; Prayuginingsih, Henik; Muliasari, Risa Martha (Universitas Muhammadiyah Jember, 2024)
Indonesia is a maritime country consisting of islands and has a vast water area with abundant natural resource potential, including fish. One way to process fish so that it doesn't rot easily is by panning. The reason for carrying out the fish processing process is so that the fish and fishery products have added value. The research method used is the hayami method to calculate added value. The basis for the initial calculation is the variable value for measuring added value for one production process such as output, input, labor, wages, average labor, raw material prices, and costs other than raw materials. The average revenue from products produced by the pindang fish agroindustry in Muncar District is IDR. 13,500/fish with an added value of Rp. 2,726/fish. The resulting value added ratio is 20.19. This means that the pindang fish business in Muncar District, Banyuwangi Regency is still profitable.